Château de Coppet - a site of modernity? - Kernev-Štrajn, Jelka (Primerjalna književnost, 2004)
Coppet, as a public and modern space, represents the peak of the 18th century salon tradition, although at the same time, it surpasses it. The Coppet discourses in some respects rose above the Romantic understanding of literature, and thereby drew close to modern concepts of art and society.
Keywords: Staël, Germaine Necher, 1766-1817; francoska književnost; French literature; literarni saloni; 18.st.; Romanticism; romantika; modernost; narodna identiteta; kulturna identiteta